Parental Resilience Following the Loss Of a Child: A Case Study of a Child Drowning in Tanjung Tambak Baru Village (Jurnal Psikologi Udayana, 2025)
This study examines the dynamics of parental resilience among individuals who have experienced the loss of a child due to drowning, a traumatic event that triggers profound grief and significant psychological distress. The main focus of this research is to understand how parents rebuild their resilience and to identify the internal and external factors that contribute to this process. This study addresses a gap in the literature, which has predominantly emphasized resilience among university students or disaster survivors, while parental resilience in the context of child loss, particularly in rural areas, remains relatively underexplored. This study employed a qualitative approach with a case study design and involved two participants from Tanjung Tambak Baru Village. Data were collected through in-depth interviews, observation, and documentation, and were analyzed using the interactive model of Miles and Huberman. The findings indicate that both participants experienced intense grief but followed different recovery pathways: one relied more on external support such as family and community, while the other drew on internal strengths including self-reflection, emotional regulation, and spirituality. Ultimately, both participants reached a stage of acceptance and were able to adapt to life after the loss of a child.
Keywords: resilience; loss; drowning